Single-stage nasolabial interpolation flap for reconstructing defects of the nose and inner corner of the eye - Jefferson Di Lamartine Galdino Amaral; Ronan Caputi Silva Dias; Amanda Costa Campos; Rafael Sabino Caetano Costa; Suellen Vieira Da-Silva; Anderson de Azevedo Damasio; Juldásio Galdino de Oliveira Júnior; José Carlos Daher (Revista Brasileira de Cirurgia Plástica)
Introduction: Interpolation flaps are effective surgical options for reconstructing skin defects in various areas of the body, including the face. The proposed flap does not require postoperative care with the pedicle exposed and can be performed in a single surgery. Objective: To evaluate the usefulness of the nasolabial interpolation island flap (NIF) for reconstructing nasal segments and the inner corner of the eye, as well as discuss improvements in its design and performance. Methods: In this retrospective study, medical records of patients with nasal defects that were repaired with a nasolabial interpolation flap were reviewed. All flaps were created with a subcutaneous tunnel to avoid pedicle exposure and prevent scar connection with the donor area and the defect. Results: Five patients aged 30-92 years were included. In all cases, intraoperative frozen biopsy revealed disease-free margins, indicating the extent of the resection. Basal cell carcinoma was found in four patients and squamous cell carcinoma in one. There were no complications such as postoperative bleeding or necrosis. Good functional and aesthetic results were achieved. Discussion: The NIF can help in the reconstruction of extensive defects of the nasal ala, tip, columella, and medial dorsum as well as the corner of the eye. We also highlight the more favorable aesthetic aspect of the pedicle in the interpolation island versus transposition flap. Conclusion: The single-stage NIF flap is a reliable option for reconstructing facial segments as it has good vascularization, can be performed in a single surgery, and can be used to cover places where few other reconstructive options are available.